Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Two new species of Atopobathynella (Parabathynellidae, Bathynellacea) from the Pilbara region, Australia - Giulia Perina; Ana I. Camacho; Melissa Danks; Nicole White; Michelle T. Guzik (Systematics and Biodiversity, 2023)

An integrated approach to explore the monophyletic status of the cosmopolitan genus Hexabathynella (Crustacea, Bathynellacea, Parabathynellidae): two new species from Rottnest Island (Wadjemup), Western Australia - Giulia Perina; Ana Camacho; Steven J.B. Cooper; Stephanie Floeckner; Alison J. Blyth; Mattia Saccò (Systematics and Biodiversity, 2023)

Novel sexual dimorphism in a new genus of Bathynellidae from Russia, with a revision of phylogenetic relationships - Ana I. Camacho; Paloma Mas‐Peinado; Sanda Iepure; Giulia Perina; Beatriz A. Dorda; Adrian Casado; Isabel Rey (Zoologica Scripta, 2020)
Bathynellidae is the neglected family of Bathynellacea, a groundwater group of crustaceans with 33 genera and 107 species described and almost half of them included in the ‘catch‐all’ genus Bathynella . Due to the morphological homogeneity of the species, the taxonomic uncertainties have accumulated over time. Therefore, to explore the phylogenetic relationships among taxa, a combined approach using morphological and molecular data is needed. In this paper, we performed a phylogenetic analysis based on partial sequences of COI and 18S including 30 species of Bathynellidae. This data set represents the most updated one, including a new genus and a new species ( Altainella calcarata gen. n. sp. n.) of Bathynellidae described here from Altai Mountain (Russia). The new taxon presents a new type of sexual dimorphisms with a peculiar structure on the coxopod of the male thoracopod VII and also sexual dimorphism on the mandibular palp, as some species of the subfamily Gallobathynellinae. This is the first species of Bathynellidae that presents both variants of sexual dimorphism. The molecular phylogeny supports the morphology and the erection of the new genus and displays highly divergent genetic units corresponding to subfamilies, with the new genus closer to Bathynellinae genera than other subfamilies. With the description of this new species and its molecular characterization, the existence of the other genera beyond Bathynella is confirmed in Eurasia.

New Bathynellidae (Crustacea) taxa and their relationships in the Fortescue catchment aquifers of the Pilbara region, Western Australia - Giulia Perina; Ana I. Camacho; Joel Huey; Pierre Horwitz; Annette Koenders (Systematics and Biodiversity, 2019)